The influence of information technology and compensation on the employees performance of the regional revenue and financial management agency - Ngantung, Rocky Marco; Masengi, Evi Elvira; Bogar, Wilson (Technium Social Sciences Journal, 2024)
The objectives of this study were 1) to determine the effect of Information Technology on performance at the Regional Financial and Revenue Management Agency (BPKPD) of Tomohon City; 2) To determine the effect of Compensation on employee performance at the Regional Financial and Revenue Management Agency (BPKPD) of Tomohon City; 3) To determine the effect of Information Technology and Compensation simultaneously on employee performance at the Regional Financial and Revenue Management Agency (BPKPD) of Tomohon City. The research method used is quantitative research method. Primary data were obtained through questionnaires distributed to 70 employees as research samples. Research data testing techniques include using validity tests, reliability tests, multiple linear regression model tests, hypothesis tests, and coefficient of determination tests. The results showed that 1) There is a positive functional influence that contributes between Information Technology and employee performance; 2) There is a positive functional influence that contributes between compensation and employee performance; 3) There is a positive functional influence that contributes between Information Technology and Compensation together on Employee Performance.